2012
DOI: 10.1525/mp.2013.30.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Expressive Versus Mechanical Musical Performance on Short-term Memory for Musical Excerpts

Abstract: , et al.. Influence of expressive versus mechanical musical performance on short-term memory for musical excerpts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…Exact pitch intervals in music (Dowling, 1991;Dowling & Bartlett, 1981;Dowling et al, 1995) are increasingly bound to the underlying rhythm and contour structure over time, such that there is improvement in memory (or no forgetting) over the course of 15-120 s. The same phenomenon is observed with homophonic music (i.e., melody plus harmony; Dowling & Bartlett, 1981;Dowling & Tillmann, 2014;Dowling et al, 2001;Tillmann et al, 2013). Memory for exact words in poetry shows similar improvements, presumably because the words are increasingly bound to the underlying rhythm over time, which explains why the effect is not evident for prose (Tillmann & Dowling, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…Exact pitch intervals in music (Dowling, 1991;Dowling & Bartlett, 1981;Dowling et al, 1995) are increasingly bound to the underlying rhythm and contour structure over time, such that there is improvement in memory (or no forgetting) over the course of 15-120 s. The same phenomenon is observed with homophonic music (i.e., melody plus harmony; Dowling & Bartlett, 1981;Dowling & Tillmann, 2014;Dowling et al, 2001;Tillmann et al, 2013). Memory for exact words in poetry shows similar improvements, presumably because the words are increasingly bound to the underlying rhythm over time, which explains why the effect is not evident for prose (Tillmann & Dowling, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…ROC curves therefore deal more efficiently with response bias especially when there is some degree of uncertainty associated with the responses. This type of measure, taking explicitly into account the uncertainty that may be associated with the responses, is very frequently used in the musical STM literature (e.g., Dewar, Cuddy, & Mewhort, 1977;Dowling & Tillmann, 2014;Halpern, Bartlett, & Dowling, 1995;Tillmann et al, 2013).…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…During the recognition phase, participants heard again the sequence of beat sounds which had the same temporal organisation as in the target sequence and a probe tone was played at one of the six serial positions; the probe was always a tone that had been presented in the target sequence. The participants were required to covertly recall the target sequence in time with the beat sequence and to make a same/different judgment relative to the position of the probe tone in the target sequence by pressing one of the six response buttons representing different levels of confidence (1 = very sure same, 2 = sure same, 3 = same, 4 = different, 5 = sure different, 6 = very sure different), as used in previous experiments on musical STM (e.g., Dowling & Tillmann, 2014;Tillmann et al, 2013). For more details about our motivation to use levels of confidence, see the Data and statistical analyses section.…”
mentioning
confidence: 99%
“…The finding of a reliable differentiation between degree of perceived tension in modulation to step 7 and to step 5 for the real music excerpts, but not for the plain harmonic progressions, corroborated the results of the previous study by Thompson and Cuddy (1997) that demonstrated that the listeners' responses to expressive performance corresponded more closely to theoretical predictions based on the circle of fifths than their responses to nonexpressive performance. This advantage for real music excerpts might be related to a better short-term memory for expressively performed music (Tillmann, Dowling, Philippe, Molin, Schulze, Poulin-Charronnat, Schoen, & Bigand, 2013). It is possible that the richer artistic contents in the real music excerpts enhanced the memorization of preceding tonal information by generating a greater emotional response (Chapin, Jantzen, Scott Kelso, Steinberg, & Large, 2010;Vieillard, Roy, & Peretz, 2012), which amplifies the intuitive comparison between the opening and the concluding tonalities in modulation.…”
Section: Several Of Our Findings Confirmed Previous Investigations Inmentioning
confidence: 99%